Ecosystem effects of bottom trawling in the Benguela current system : experimental and retrospective data analyses - Mafwila, Samuel Kakambi (Department of Biological Sciences, 2015)
This thesis investigates ecosystem effects of bottom-trawling on demersal fish assemblages (1990-2006) off Namibia and their relationship to environmental variables.